2017
DOI: 10.5846/stxb201509151898
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of microbial community in forest soil between rhizosphere and non-rhizosphere in summer and autumn in Qinling Mountains, China

Abstract: 收稿日期:2015• 09• 15; 网络出版日期:2016• 07• 13 * 通讯作者 Corresponding author.E•mail: wxhe1968@ 163.com DOI: 10.5846 / stxb201509151898 曹永昌,杨瑞,刘帅,王紫泉,和文祥,耿增超.秦岭典型林分夏秋两季根际与非根际土壤微生物群落结构.生态学报,2017,37(5) :1667• 1676. Cao Y C,Yang R,Liu S,Wang Z Q,He W X,Geng Z C.Characteristics of microbial community in forest soil between rhizosphere and non•rhizosphere in summer and autumn in Qinling Mountains, China.Acta Ecologica Sinica,2017,37(5) :1667• 1676.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this study, the differences in bacterial diversity and richness of three halophytes rhizosphere soil showed that P. communis was significantly higher than A. sinensis, which was caused by the unique physiological process of different plants. Studies had shown that abscission and secretion were positively correlated with the growth of plant roots, the more vigorous the growth of plant roots, the more abscission and secretion in soil (Cao et al, 2017). Compared with the other two halophytes, the rhizome of P. communis is larger, sturdy, and well-developed, which makes the bacterial community in the rhizosphere soil of P. communis have higher diversity and richness.…”
Section: Effects Of Different Halophytes In the Rhizosphere And Bulk Soils On Bacterial Community Diversitymentioning
confidence: 99%
“…In this study, the differences in bacterial diversity and richness of three halophytes rhizosphere soil showed that P. communis was significantly higher than A. sinensis, which was caused by the unique physiological process of different plants. Studies had shown that abscission and secretion were positively correlated with the growth of plant roots, the more vigorous the growth of plant roots, the more abscission and secretion in soil (Cao et al, 2017). Compared with the other two halophytes, the rhizome of P. communis is larger, sturdy, and well-developed, which makes the bacterial community in the rhizosphere soil of P. communis have higher diversity and richness.…”
Section: Effects Of Different Halophytes In the Rhizosphere And Bulk Soils On Bacterial Community Diversitymentioning
confidence: 99%